Similar hemoglobin mass response in hypobaric and normobaric hypoxia in athletes - Hauser, A.; Schmitt, L.; Troesch, S.; Saugy, J. J.; Cejuela-Anta, R.; Faiss, R.; Robinson, N.; Wehrlin, J. P.; Millet, G. P. (Medicine & Science in Sports & Exercise, 2016)
Purpose: To compare hemoglobin mass (Hbmass) changes during an 18-d live high-train low (LHTL) altitude training camp in normobaric hypoxia (NH) and hypobaric hypoxia (HH).